Gambling on the market: The role of for-profit provision in early childhood education and care - Penn, Helen (Journal of early childhood research : ECR, 2011)
Since 1997 there has been an unprecedented expansion of the childcare for-profit market in the UK. The repercussions of this for understanding of ‘quality’ and definitions of good practice for early education and care have barely been explored. But in the current economic recession the market is now beginning to shrink, and there is considerable turnover of nursery places. The built-in instability of the for-profit market serves to highlight its problematic nature and difficulties of relying on it as a vehicle for delivering government policies. This article explores the economic rationales for and the limitations of a market approach to early education and care services. It considers the direct and indirect research evidence about the functioning of such a market. It argues that any conceptualization of early childhood services in the UK now has to take account of the growth of the for-profit childcare market and the economic rationales of the marketplace.